Pengaruh Rasio Hydroxyapatite–Tricalcium Phosphate pada Lapisan PEO terhadap Stabilitas Korosi Paduan Mg-AZ31B untuk Implan Biomedis - Nadira Ghina Azzahra; Muhammad Ridwan (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The magnesium alloy AZ31B is increasingly used in biomedical applications, particularly as an implant material, due to its relatively low aluminum content and mechanical properties that closely resemble those of bone. Additionally, AZ31B exhibits corrosion resistance that is suitable for biological environments. These properties make it a promising material for bone implants. However, one of the main challenges in using magnesium is its high degradation rate in the body, which can affect the stability and function of the implant. Therefore, surface modification is necessary to control the degradation rate and enhance the material’s durability. One effective method to reduce the corrosion rate of AZ31B is the Plasma Electrolytic Oxidation (PEO) technique. PEO can form a hard, protective oxide layer on the surface of the metal, which helps improve its corrosion resistance. This study aims to explore the effect of the mass composition of hydroxyapatite (HAp) and tricalcium phosphate (TCP) on the PEO coating formed on the AZ31B substrate. The compositions used in this study were 70%:30%, 50%:50%, 40%:60%, and 60%:40%, with an electrolyte solution containing Na₂SiO₃ (2.5 g/L) and KOH (2 g/L). Corrosion characteristics of the coating were evaluated using two methods: weight loss and polarization tests. The results showed that the 70%:30% HAp:TCP composition provided the most optimal results. The polarization test recorded a corrosion rate of 0.22 mpy, while the weight loss test showed a corrosion rate of 0.29 mpy. These findings indicate that the PEO coating with the 70%:30% HAp:TCP composition effectively reduces the corrosion rate of AZ31B, enhancing its potential for biomedical implant applications, particularly in environments where corrosion resistance is crucial for long-term performance in the body.